Preparation of Porous Silk Fibroin Materials Cross-linked by Carbodiimide (EDC) (Journal of Fiber Bioengineering and Informatics, 2009)
A cross-linked porous silk fibroin (SF) material was prepared by freeze-drying.1-ethyl-3- (3-dimethylaminopropyl) carbodiimide hydrochloride (EDC), N- hydroxysuccinimide (NHS) and 2-morpholinoethanesulfonic acid (MES) were added in different concentrations of SF solutions. The mixed solution was poured into aluminum vessels to make a layer of about 2 mm thickness. Then they were frozen for 6 hrs at -80, -50, -20 and -10 °C, respectively, and lyophilized. After 36 hrs porous silk fibroin materials were obtained. Compared to the uncross-linked porous SF materials, cross-linked materials show an obvious decrease in water solubility, indicating that effective cross-linking reaction took place in silk fibroin. The results of FT-IR and Raman spectra show that EDC reacted with the carboxyl of SF, mediating acyl isourea or acid anhydride formation. The resultant acid anhydride may readily react with amino groups of SF to yield amide bonds. The influence of freezing temperature and concentration of the silk fibroin solution on the structure and properties of materials were also investigated. The porous SF materials, with average pore size 32.0-332.5